IN VITRO ANTICANCER AND ANTI-LIPOXYGENASE ACTIVITIES OF CHIA SEED OIL AND ITS BLENDS WITH SELECTED VEGETABLE OILS - Gazem, Ramzi Abdulrashed Abdulkhaleq; Ramesh Puneeth, Honnalagere; Shivmadhu Madhu, Chakkere; Chandrashekaraiah Sharada, Angatahalli (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Â Â Objective: To investigate the anticancer and anti-inflammatory potential of chia seed oil (CSO) and its blends in vitro. Methods: The in vitro cancer cytotoxic properties ability of CSO and its blends was evaluated by (3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide) (MTT) and trypan blue assays using major cell lines including chronic myelogenous leukemia, HeLa and MCF-7 cells. The anti-inflammatory effect of the CSO and its blends was studied by assessing the anti-lipoxygenase (LOX) activity in vitro. Results: Incubation with CSO alone significantly inhibited the LOX activity. In the combination groups, CSO slightly increased the inhibition among blends of soybean and palmolein oils. In addition, CSO alone and in blends demonstrated potent and differential anticancer activity in MTT and trypan blue assays. Conclusion: Our results pave the way for the conclusion that CSO alone or in combination with the vegetable oils proves to be a healthy synergistic supplement or an adjuvant for the current diet. The supplementation with CSO is suggested for the modern lifestyle to delay or prevent the incidence of degenerative disorders.